Begonia fimbritepala (Begoniaceae), a new species endemic to the Atlantic Coastal Forest in the state of Rio de Janeiro, Brazil - Jacques, Eliane De Lima (Phytotaxa, 2020)
Begonia fimbritepala (Begoniaceae) a new endemic species to the Atlantic Coastal Forest of Brazil is described and illustrated. This species resembles B. olsoniae in occupying the same habitat (rocky slopes and outcrops), and in the shape of the leaf blades and size of male flowers. It differs by glabrous leaves on the adaxial surface, villous abaxial veins with simple trichomes (vs. hispid on both surfaces, squamulose on abaxial veins with fimbriate scales) and tepals with ciliate margins (vs entire to slightly crenulate).